2016
DOI: 10.3747/co.23.2881
|View full text |Cite
|
Sign up to set email alerts
|

Is Clinical Breast Examination Important for Breast Cancer Detection?

Abstract: Background Screening clinical breast examination (cbe) is controversial; the use of cbe is declining not only as a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 42 publications
2
57
0
1
Order By: Relevance
“…In contrast with cancers detected by mammography alone, those detected by clinical breast examination had more aggressive features. Clinical breast examination (CBE) is a low-cost assessment that could improve the detection of breast cancer and could prompt breast ultrasonography in the case of a negative mammogram (11).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with cancers detected by mammography alone, those detected by clinical breast examination had more aggressive features. Clinical breast examination (CBE) is a low-cost assessment that could improve the detection of breast cancer and could prompt breast ultrasonography in the case of a negative mammogram (11).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly for women less than 50 and more than 69 years of age, in the moderate‐ and high‐risk groups, it is recommended that CBE should be a part of routine periodic examinations by trained healthcare professionals (Provencher et al. ) and in older women (Jatoi ; Schwab et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…CBE is a low cost tool advocated widely in low-resource and middle-resource countries (Anderson et al 2011;Gelband et al 2016). Particularly for women less than 50 and more than 69 years of age, in the moderate-and high-risk groups, it is recommended that CBE should be a part of routine periodic examinations by trained healthcare professionals (Provencher et al 2016) and in older women (Jatoi 2015;Schwab et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The decision was based on clinical experience, expected risks and benefits 9 , and current opposing guidelines. Recently, a retrospective study concluded that a significant number of cancers would have been missed if clinical breast exams had not been performed 61 .…”
Section: Discussionmentioning
confidence: 99%